2019
DOI: 10.3389/fmicb.2019.00952
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Analogues as Antibacterial Agents

Abstract: The rapid increase in antibiotic-resistant bacteria has emphasized the urgent need to identify new treatments for bacterial infections. One attractive approach, reducing the need for expensive and time-consuming clinical trials, is to repurpose existing clinically approved compounds for use as antibacterial agents. Nucleoside analogues are commonly used for treating viral and fungal infections, as well as for treating cancers, but have received relatively little attention as treatments for bacterial infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 93 publications
5
110
0
2
Order By: Relevance
“…Among them, the cytidine analogue gemcitabine was reported to be 6th on the list of broad-spectrum antivirals that show in vitro activities . Additionally, it was recently reported that several nucleoside analogues clinically approved as antivirals or antineoplastic agents also show antibacterial activity (Thomson and Lamont, 2019). Examples of such drugs include gemcitabine, zidovudine, 5-fluorouracil, floxuridine, idoxuridine and thiopurines.…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, the cytidine analogue gemcitabine was reported to be 6th on the list of broad-spectrum antivirals that show in vitro activities . Additionally, it was recently reported that several nucleoside analogues clinically approved as antivirals or antineoplastic agents also show antibacterial activity (Thomson and Lamont, 2019). Examples of such drugs include gemcitabine, zidovudine, 5-fluorouracil, floxuridine, idoxuridine and thiopurines.…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
“…Additionally, treatment with gemcitabine activates the expression of several IFN-stimulated genes (including CXCL10, IRF7, IRF9, IFIT1 or DDX58), the major effectors in innate immunity . Gemcitabine has also shown antibacterial activity against grampositive bacteria, such as Enterococcus, Listeria, Bacillus, and Staphylococcus, including multi-drug-resistant strains of Staphylococcus aureus (Thomson and Lamont, 2019;Jordheim et al, 2012;Sandrini et al, 2007). Unfortunately, one study revealed that the treated strains developed resistance to gemcitabine.…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these analogues have been proposed as an alternative to antibiotics as a consequence of resistance emergence (Thomson and Lamont, 2019). Nucleoside analogues have the advantage of being clinically approved for cancer therapies, but also as antiviral and antifungal treatments (Thomson and Lamont, 2019). Pyrimidine and purine analogues, as we use here, show potent antimicrobial activity against S. aureus in the past (Rogers and Perkins, 1960;Stickgold and Neuhaus, 1967;Jordheim et al, 2012a; Thomson and Lamont, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…We hypothesised that the response to pexiganan sensitizes S. aureus against certain nucleoside antimetabolites or toxic nucleoside analogues. Interestingly, these analogues have been proposed as an alternative to antibiotics as a consequence of resistance emergence (Thomson and Lamont, 2019). Nucleoside analogues have the advantage of being clinically approved for cancer therapies, but also as antiviral and antifungal treatments (Thomson and Lamont, 2019).…”
Section: Introductionmentioning
confidence: 99%